Decreased survival in hepatitis C patients with monomorphic post-transplant lymphoproliferative disorder after liver transplantation treated with frontline immunochemotherapy. Issue 9 (2nd September 2018) - Alderuccio, Juan Pablo; Stefanovic, Alexandra; Dammrich, Daniel; Chapman, Jennifer R.; Vega, Francisco; Selvaggi, Gennaro; Tzakis, Andreas; Lossos, Izidore S.
Abstract: Post-transplant lymphoproliferative disorder (PTLD) develops in 1–3% of liver transplant recipients and no consensus exists about therapeutic management. From 2006 to 2016, 1489 liver transplants were performed at our institution with 20 patients (incidence 1.3%) developing PTLD. Hepatitis C virus (HCV) was the leading cause ( n  = 10) of liver transplant in PTLD patients. Diffuse large B-cell lymphoma was the most frequent histologic subtype ( n  = 17), and we report our experience in the management of these patients. Patients were treated with frontline immunochemotherapy without immunosuppression reduction. All evaluable patients achieved a complete remission. Statistically significant decreased survival was identified in HCV-positive patients. Six patients (60%) exhibited increases in HCV RNA levels during therapy. Four patients (40%) developed graft failure and three of them (30%) died from liver dysfunction. This is the first study providing evidence of decreased survival in HCV-positive PTLD patients after liver transplant receiving immunochemotherapy.